Evaluation of Long Term Respiratory Complications in Childhood and Adolescent Cancer Survivors - Fırat Ergin; Nazan Çetingül; Esen Demir; Abdullah Sayıner; Hüdaver Alper; Figen Gülen (Journal of Pediatric Research, 2023)

(untitled)
Aim:In addition to increased survival rates, systemic complications which can impair the quality of life have been seen in 25-30% of childhood and adolescent cancer cases. The respiratory system is one of the severely affected systems. We aimed to evaluate late respiratory complications and risk factors in pediatric and adolescent cancers.Materials and Methods:We examined the pulmonary complications of 50 cancer patients and 40 control cases. We asked about environmental exposures, physical examinations performed, and pulmonary function tests (PFT) spirometry, diffusing capacity of the lungs for carbon). X-ray was performed on all patients in the patient group and on patients with indications in the control group.Results:In the patient group, there was impairment of pulmonary function in 52%, [24% small airway disease (SAD)], 14% diffusion disorders (DD) and 14% combined disorders (CD) compared to 22.5% in the control group (p=0.007). There was a higher risk of restrictive disorder and/or SAD in those cancer patients who were diagnosed prior to 2 years of age. Additionally, there was a higher rate of SAD in those patients with soft tissue sarcomas and a higher rate of restrictive disease in those patients who had received high-dose alkylating agents. No significant PFT impairment was observed in the other patient groups.Conclusion:There is a high incidence of respiratory impairment in childhood and adolescent cancer survivors. They need to be followed up by a multidisciplinary team and be informed about the additional risk factors which may cause lung function loss.